Low-cost electromyography – Validation against a commercial system using both manual and automated activation timing thresholds. (October 2018) - Heywood, Sophie; Pua, Yong Hao; McClelland, Jodie; Geigle, Paula; Rahmann, Ann; Bower, Kelly; Clark, Ross
Abstract: Widespread use of electromyography (EMG) as an assessment and biofeedback method may be limited by costly commercial systems. Low-cost devices are available; however their validity is unknown. This study determined the concurrent validity of a low-cost EMG on a microchip compared with a commercially available system during isometric and dynamic muscle contractions. Inter-tester, intra-session reliability of manual data extraction during data processing compared to a simple, automatic thresholding method using the Teager-Kaiser energy operator (TKEO) was also evaluated. 10 healthy women (age 28.1 ± 6.8 yrs, height 162.1 ± 6.8 cm, mass 60.3 ± 10.2 kg) were assessed simultaneously with a commercially available EMG system (Telemyo DTS) and a custom low-cost EMG system (Myoware Muscle Sensor) during voluntary isometric contractions, knee extension, squatting, stepping and jumping. Two surface electrode sets (connected to the low-cost and the commercial system) were placed end to end along the same Vastus Lateralis muscle fibre line. Peak and mean contraction intensity, and contraction duration were analysed. Overall the relative agreement between systems was excellent for peak muscle activation (ICC 0.77–0.96) and modest to excellent for mean muscle activation (ICC 0.68–0.95) and contraction duration (ICC 0.65–0.99). Inter-tester, intra-session reliability was excellent for peak contraction intensity (ICC > 0.99) and modest to excellent for mean contraction intensity, with the TKEO method primarily recording stronger agreement than the manual method. Poor to excellent inter-tester reliability occurred for contraction duration. Our findings indicate that a low-cost EMG system is comparable to a commercial system for assessing muscle activation, and that using the TKEO improved the reliability of timing related variables.